Implementation of Task-Based Language Learning in Improving Reading Ability in Class 8 of MTsN 9 Boyolali - Titik Murdianasari; Muhammad Nur Habibi (Teaching English and Language Learning English Journal, 2026)
Reading comprehension is a fundamental skill in English language learning, as it enables students to construct meaning, access information, and develop overall communicative competence. However, many junior high school students still face difficulties in reading due to limited vocabulary, weak grammatical understanding, and low engagement in teacher-centered classrooms. Therefore, this study aims to examine the effectiveness of Task-Based Language Learning (TBLL) in improving students’ reading comprehension skills. This study employed a quantitative experimental method using a one-group pretest–posttest design. The participants were 25 eighth-grade students of MTsN 9 Boyolali. Data were collected through reading comprehension tests on advertisement texts and analyzed using descriptive statistics and normalized gain (N-Gain) analysis. The results showed a significant improvement in students’ reading performance after the implementation of TBLL. The average score increased from 65.2 in the pretest to 79.6 in the posttest, with an average N-Gain score of 0.4, indicating a medium level of improvement. The greatest improvement was found in the linguistic component, followed by diction, goal, and message. In conclusion, the findings indicate that TBLL is an effective instructional approach for enhancing students’ reading comprehension. By promoting communicative, collaborative, and student-centered learning, TBLL supports meaningful interaction and active engagement, which contribute positively to students’ reading development.